MENGANALISIS PEMBELAJARAN IPS DENGAN MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBER HEAD TOGETHER (NHT)” - Siti Asmaul Husna; Sedya Santosa; Lailatul Husna Al-Illahiyah; Liza Septiani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to describe the success of the Number Head Together (NHT) cooperative learning model through strategies that can increase student involvement in the learning process. This model encourages students to work together in groups, discuss with each other, and share information before answering questions from the teacher. The teacher in the learning process is less modified in this social science learning method. This can happen in the learning mindset which is interpreted as the acquisition of knowledge to students, learning is emphasized on results, not on the process. As a result, learning in class becomes monotonous because the teacher delivers material through notes and memorization. Qualitative and descriptive methods are used to collect data through observation, interviews, and document studies. The results are that students have improved in Numbered Head Together learning, including: 1) student learning activities are quite good. 2) students find it easier to understand learning materials. 3) it is necessary to exemplify how to teach using an active student learning model, 4) the teaching aids used support the achievement of the learning objectives set.